Rule of law, legal culture, education and academic integrity - Ye. V. Duliba; O. Ye. Avramova; A. M. Kulish; V. V. Myrhorod-Karpova (Bulletin of Kharkiv National University of Internal Affairs)
Comparing the 2021 Rule of Law Index, 2021 Legatum Prosperity Index, 2021 Education Rankings by Country, 2021 Times Higher Education, 2021 QS World University Rankings has demonstrated that there is a clear correlation between adherence to the rule of law in the state and the legal culture, education and academic integrity. It is proved that the higher the level of adherence to the rule of law, the higher is the level of legal culture and, accordingly, the level of quality of education and observance of academic integrity.